The Influence of Corporate Governance on Financial Performance With Bank Risk Taking As a Moderating Variable - Jesslyn Jesslyn; Mariska Ramadana; Anita Anita (International Journal of Economics and Management Research, 2024)
This study aims to examine the effect of CEO power, foreign ownership, independence, and voting rights on financial performance in banks with risk-taking as a moderating variable after the financial crisis in 2007-2008. The method used is quantitative using secondary data. The research data source uses the financial statements of Indonesian companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. Sample collection used a purposive sampling approach. Data was obtained from the company’s financial reports on IDX and official websites. Data analysis uses panel data regression. The author found that CEO power, independence, and bank risk taking had a significant negative effect on the financial performance of banks, while foreign ownership and voting rights did not have an effect on financial performance of banks. This study contributes to the literature on bank governance and risk-taking. The purpose of this empirical analysis is to examine in detail the subject and the dynamics among these variables in the macroeconomic environment of the financial system, particularly with regard to the regulatory and supervisory framework after the financial crisis in 2007-2008.